Possibilites for revitalizing the Itelmen language, Kamchatka, Russia, 2013-2016 - Tatiana Degai (Arctic Data Center, 2017)
This project research was conducted in Kamchatka, the Pacific coast of Russia among Itelmen people - an indigenous minority group with a severely endangered language. The project documented and evaluated a range of ongoing efforts to revitalize Itelmen and analyzed the effectiveness of the existing language revitalization tools and programs. This research was conducted in order to contribute to a deeper understanding of language and cultural revitalization programs not only among Itelmens of Kamchatka, but also with the purpose to inform about these programs world-wide. The preservation of this language in the face of centuries of assimilation programs enacted by Russian Imperial and later Soviet administrations is significant. The most significant broader impact is what other Indigenous communities in a similar situation to the Itelmen can learn from this community's struggles and efforts as well as what Itelmens can learn from other communities that are struggling to save their language. Researchers on this project aimed to understand which methods should be applied for a successful Itelmen language revitalization program both in class and outside the classroom. When this research started in 2013 there were about nine speakers who were growing up speaking Itelmen as their first language. By the end of the study in 2016 only four speakers remained. In Kamchatka the student researcher visited five different locations. Each has its own specifics. Part of the research was dedicated to the use of multimedia in language revitalization. The main outcome of this part of the project was the publication of the DVD of Itelmen traditional and contemporary songs with subtitles and video Xaƚc mǝncaⱪa’ƚkicen (Let's sing). The idea was borrowed from the widely known Karaoke. Each song has a voice of the native speaker singing the song, visualized by subtitles in Itelmen and Russian, and video. This research indicated that Itelmens are ready to be active in bringing their language back to the active life, however there is a great lack of knowledge about the language immersion methodologies and other techniques that go beyond the educational setting of schools.